Modifications Of The Non-Linear Parameters Of The Heart Rate Variability Related To The Mental Arithmetic Test - Pedraza-Rodríguez, Elys María; Almira-Gómez, Carlos Rafael; Cortina Reyna, Sergio; Bueno-Revilla, David de Jesús; López-Galán, Erislandis; Sánchez-Hechavarría, Miguel Enrique (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: The autonomic nervous system has been related to an increase in heart rate, blood pressure and cardiac output in situations of stress. Objective: To determine the modifications that the non-linear parameters undergo in the autonomic cardiovascular regulation of the heart rate variability subjected to mental stress through the mental arithmetic test. Material and Method: A non-observational quasi-experimental study of before-after type without control group was conductedin the Biomedical Basic Sciences Laboratory at Medical school 1, University of Santiago de Cuba, from March 2016 to August 2018. A group of 10 Medical Students constituted the population and sample. Results: Statistically significant differences between means were found in Heart rate values (p = 0.000), SD1 (p = 0.002), SD2/SD1rate (p = 0.000), Sample Entropy (p = 0.026), Short-term fluctuations α 1 (p = 0.000), CorrelationDimension (p = 0.020), Max line length (p = 0.017), Recurrence rate (p = 0.007), Determinism (p = 0.003), Multiscale Entropy minimum(p = 0.001), Multiscale Entropy maximum(p = 0.000) and MultiscaleEntropyAverage (p = 0.001). Conclusions: The non-linear parameters in the cardiovascular autonomic regulation of Heart rate, SD1, SD2/SD1 rate, Sample Entropy, Short-term fluctuations α 1, Correlation Dimension, Max line length, Recurrence rate, Determinism, Multiscale Entropy Minimum, Multiscale Entropy Maximum and Multiscale Entropy Average experienced variations in patients subjected to mental stress through the arithmetic calculation test.